Golden Era of PB: Who Reaped the Fruits of Growth? - Jinkook Lee (Korea Development Institute (KDI), 2017)
The rise of the market for private-label brands (PB) has elevated the profits of corporate retailers but has not significantly affected, or in some cases reduced, those of subcontracting manufacturers. This is not only due to the significant cannibalization effect on national brands (NB) caused by the release of similar PBs, but also because the imbalance in the bargaining positions of retailers and manufacturers has caused operating profits to be set low while retail margins are set high. Accordingly, the time has come to prioritize the establishment of a fair trade order to promote the balanced development of the PB business. Violations of the ban on requesting management information on manufacturers must be closely examined and stronger punishment and penalties are needed for violations against the Act on Fair Transactions in Large Franchise and Retail Business. Additionally, manufacturers need to actively utilize government programs designed to support sales channels and to seek ways to advance into overseas markets. - Private brands (PB) have exhibited a remarkable expansion based on product diversity and quality enhancement. - This study analyzes the effect of increased PB sales on the growth of the retail and manufacturing industries and suggests policy directions for shared growth and fair market order. - The PB market grew significantly from 3.6 trillion won in 2008 to 9.3 trillion won in 2013. - Large discount stores gave rise to the PB market but convenience stores are currently leading the sales growth. - Domestic retailers' share of PB sales has grown to a similar level as global leaders and there is potential for future growth. - The recent growth of general retail has been heavily dependent on the growth of corporate retailers. - The increase in corporate retailers' sales points to an increase in purchasing power. - The increase in buyers' power resulting from market concentration in general retail is a prerequisite to the release of PBs. - The intensifying competition between retailers increases economic incentives to produce PBs. - PBs are a profit-maximizing strategy created within the structure changes prompted by corporate retailer-centered market concentration and the intensifying competition between them. - An increase in the PB sales share increases both sales and operating profit of retailer stores. - 1,000 manufacturing suppliers to corporate retailers were interviewed and the economic effects of expanding the supply of PBs were analyzed. - Large firms experienced a drop in total sales due to the cannibalization effect of their own products as the share of PB sales increased. - Micro businesses experienced a weaker cannibalization effect, and PB supply helped them to secure sales channels and increase the capacity utilization rate, which increased sales. - No significant increases in operating profit were observed in micro businesses. - In supplying PBs, SMEs and micro businesses have a smaller operating profit ratio and larger retail margin ratio than in supplying NBs. - The unfavorable profit sharing structure for SMEs and micro businesses is possibly incurred by the imbalance in bargaining position. - Of 309 PB suppliers, 30 firms (9.7%) experienced unfair trade requests from retailers, and the most common is cutting the supply price (20 firms, 34%). - The Fair Trade Commission should closely examine any violations of the ban on requesting information on production costs. And heavier punishment should be imposed on any violations of the Act on Fair Transactions in Large Franchise and Retail Business. - SME manufacturers need to step beyond the narrow domestic market into larger PB markets abroad by actively utilizing government's support programs.
Keywords: 330